Online Learning in University: Pros and Cons of Study - Nanik Hindaryatiningsih (Journal of Innovation in Educational and Cultural Research, 2023)
The purpose of this study was to determine the advantages and disadvantages of implementing online learning in the Economics Education study program. The research method used is a qualitative case study. Economics Education students and teachers were used as informants in this study. Data was collected using an online questionnaire (google-form), observation, and documents. Data analysis was carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The research findings show that the disadvantages of online learning at Halu Oleo University outweigh the benefits. Several factors were found that both hindered and supported the success of online learning, including social factors from peers and parents, the completeness of technology learning tools, as well as the physical and psychological readiness of students and parents. So, it can be concluded that universities must pay attention to and prepare for all online learning needs. The results of this study have implications for lecturers that online learning has complex challenges and must know the needs, online learning facilities, readiness of human resources, and digital competence of teachers and students.